Knock: a study in medical cynicism. Issue 1 (1st June 2002) - Bamforth, I
Abstract : French literature has shown an enduring fascination with the social figure of the doctor. In Jules Romains' amusing play Knock (1922), and in its later film version (1951), the doctor as deceiver returns to centrestage with a flourish. Molière's seventeenth-century figures were mostly quacks and mountebanks; Knock is something new: he is a health messiah. By enforcing a mental and social hygiene based on fear, Knock brings a small rural population under his sway. Insouciance is banished by artful consciousness-raising. A society mobilises under the banner of medicine. But who is Dr Knock?